A “Ct contrast”-based strain-specific real-time quantitative PCR system for Lactobacilllus paracasei subsp. paracasei NTU 101 - Chih-Hui Lin; Tsung-Wei Shih; Tzu-Ming Pan (Journal of Microbiology, Immunology and Infection, 2018)
Background/Purposes: Routine cell number determination for specific Lactobacillus strain by cultivation requires at least 4–7 days. Thus rapid and specific cell number determine methods such as strain-specific quantitative PCR (qPCR) are valuable. However, qPCR method is vulnerable to difficult PCR target such as dimer/secondary structure forming sequence. Methods: In this study, a two-component, “Ct contrast” approach was applied to strain-specific qPCR system following the development of Lactobacillus paracasei subsp. paracasei NTU 101 (NTU 101) strain-specific PCR with random amplification of polymorphic DNA (RAPD)-derived strain-specific sequences. Results: The quantitative range of the NTU 101 strain-specific qPCR system was 3.0 × 101 to 3.0 × 105 copies for pure cultures, and 3.0 × 102 to 3.0 × 105 copies for multi-strain or unknown food samples. The results of spike in test and real sample testing suggested that non-specific weak background signals did not compromise test specificity, and demonstrated the potential of the NTU 101 strain-specific qPCR system in food samples. Conclusion: The two-component, “Ct contrast” approach is useful for qPCR discrimination when no ideal PCR target is available or the variance of the target site is unpredictable. The Ct contrast approach might provide a simple and robust solution for other challenging qPCR targets. Keywords: RAPD, Strain-specific, qPCR, Lactobacillus, Probiotics